Enhancing the biosynthesis of polyunsaturated fatty acids by Rhodotorula mucilaginosa and Lodderomyces elongisporus - Amera A. Abaza; Yousseria M. Shetaia; Noha M. Sorour; Ashraf S. A. El-Sayed; Ashraf F. El-Baz (Bioresources and Bioprocessing, 2024)
Abstract Single-cell oils (SCO) produced by oleaginous yeast hold promise as a sustainable alternative for producing nutritionally and pharmaceutically valuable lipids. However, the accumulation of oils varies substantially between yeast spp. Consequently, identifying well-suited producers with a high innate capacity for lipids biosynthesis is paramount. Equally important is optimizing culturing and processing conditions to realize the total lipids production potential of selected strains. The marine Rhodotorula mucilaginosa and Lodderomyces elongisporus yeast were investigated to explore their potential for polyunsaturated fatty acids (PUFAs) production on high glucose media (HGM) using two-stage culture mode. Both strains accumulated > 20% (w/w) of their dry cell weight as lipids when grown on HGM using a two-stage culture system. Both yeast isolates exhibited a maximal lipid/biomass coefficient (YL/X) of 0.58–0.66 mg/mg at 7 °C and 0.49–0.53 mg/mg at 26 °C when grown on 8% glucose and produced monounsaturated and PUFAs similar to that of Menhaden and Salmon marine oils. For the first time, significant amounts of Eicosapentaenoic acid (19%) and Eicosadienoic acid (19.6%) were produced by L. elongisporus and R. mucilaginosa, respectively. Thus, the SCO derived from these wild strains possesses significant potential as a substitute source for the industrial-scale production of long-chain PUFAs, making them a promising contender in the market. Graphical Abstract